A single intramuscular injection of rAAV‐mediated mutant erythropoietin protects against MPTP‐induced parkinsonism. (28th November 2012) - Dhanushkodi, A.; Akano, E. O.; Roguski, E. E.; Xue, Y.; Rao, S. K.; Matta, S. G.; Rex, T. S.; McDonald, M. P.
<x xml:space="preserve">Abstract</x> Erythropoietin (Epo) is neuroprotective in a number of preparations, but can lead to unacceptably high and even lethal hematocrit levels. Recent reports show that modified Epo variants confer neuroprotection in models of glaucoma and retinal degeneration without raising hematocrit. In this study, neuroprotective effects of two Epo variants (EpoR76E and EpoS71E) were assessed in a model of Parkinson's disease. The constructs were packaged in recombinant adeno‐associated viral (rAAV) vectors and injected intramuscularly. After 3 weeks, mice received five daily injections of 1‐methyl‐4‐phenyl‐1, 2, 3, 6‐tetrahydropyridine (MPTP) and were killed 5 weeks later. The MPTP‐lesioned mice pretreated with rAAV.eGFP (negative control) exhibited a 7‐ to 9‐Hz tremor and slower latencies to move on a grid test (akinesia). Both of these symptomatic features were absent in mice pretreated with either modified Epo construct. The rAAV.eGFP‐treated mice lesioned with MPTP exhibited a 41% reduction in tyrosine hydroxylase (TH)‐positive neurons in the substantia nigra. The rAAV.EpoS71E construct did not protect nigral neurons, but neuronal loss in mice pretreated with rAAV.EpoR76E was only half that of rAAV.eGFP controls. Although dopamine levels were normal in all groups, 3, 4‐dihydroxyphenylacetic acid (DOPAC) was significantly reduced only in MPTP‐lesioned mice pretreated with rAAV.eGFP, indicating reduced dopamine turnover. Analysis of TH‐positive fibers in the striatum showed normalized density in MPTP‐lesioned mice pretreated with rAAV.EpoS71E, suggesting that enhanced sprouting induced by EpoS71E may have been responsible for normal behavior and dopaminergic tone in these mice. These results show that systemically administered rAAV‐generated non‐erythropoietic Epo may protect against MPTP‐induced parkinsonism by a combination of neuroprotection and enhanced axonal sprouting.